'Even though a man takes the major role, he has no right to abuse': future male leaders' views on gender-based violence in Sri Lanka - Elisabeth Darj; Kumudu Wijewardena; Gunilla Lindmark; Pia Axemo (Taylor & Francis Group, 2017)
Background: Distinct gender roles influence gender inequality and build the foundation for gender-based violence. Violence against women is a major public health problem in all societies, and a violation of human rights. Prevalence surveys on gender-based violence have been published from Sri Lanka, but qualitative studies on men's perceptions are lacking. Objectives: The aim of this study was to explore young educated Sri Lankan men's perceptions of violence against women. Methods: Seven focus-group discussions were held. Men at the end of their university studies were purposefully selected. A topic guide was used, covering various scenarios of violence against women. Qualitative content analysis was carried out. Results: Four categories were developed through the analytic process: fixed gender roles - patriarchal values are accepted in society, female mobility control, and slowly changing attitudes; violence not accepted but still exists - sexual harassment exists everywhere, different laws for different people, female tolerance of violence, and men's right to punish; multiple factors cause violence - alcohol, violent behavior is inherited, violence culturally accepted, low education, and lack of communication; and prevention of violence against women - both parents must engage and socialize girls and boys equally, life skills education, premarital counselling, working places value clarification, and more women in politics and boards are suggested. Conclusions: Medical and management students, possible future male leaders of the country, have suggestions of prevention strategies in life skills to reduce gender-based violence and to increase knowledge of health consequences with the aim of changing attitudes.